2016
DOI: 10.1177/0271678x16669366
|View full text |Cite
|
Sign up to set email alerts
|

Inverse relationship between brain glucose and ketone metabolism in adults during short-term moderate dietary ketosis: A dual tracer quantitative positron emission tomography study

Abstract: Ketones (principally β-hydroxybutyrate and acetoacetate (AcAc)) are an important alternative fuel to glucose for the human brain, but their utilisation by the brain remains poorly understood. Our objective was to use positron emission tomography (PET) to assess the impact of diet-induced moderate ketosis on cerebral metabolic rate of acetoacetate (CMRa) and glucose (CMRglc) in healthy adults. Ten participants (35 ± 15 y) received a very high fat ketogenic diet (KD) (4.5:1; lipid:protein plus carbohydrates) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
127
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(139 citation statements)
references
References 50 publications
10
127
2
Order By: Relevance
“…Moreover, Castellano et al recently reported that a 3-month aerobic training (brisk walking) programme increased brain cell ketone utilization in patients with AD threefold without affecting cerebral glucose utilization 144 , which may be one reason that aerobic exercise can protect the brain against AD. That IF may be another approach for subjects at risk of or with AD is suggested by a study using 11 C-acetoacetate positron emission tomography (PET) imaging that showed that within 48 hours of the onset of fasting, there is a sevenfold to eightfold increase in brain uptake of ketones 4,145 . Moreover, whereas brain cell uptake of glucose is severely impaired in patients with AD, the cells remain capable of utilizing ketones 146 .…”
Section: Ims and Neurological Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Castellano et al recently reported that a 3-month aerobic training (brisk walking) programme increased brain cell ketone utilization in patients with AD threefold without affecting cerebral glucose utilization 144 , which may be one reason that aerobic exercise can protect the brain against AD. That IF may be another approach for subjects at risk of or with AD is suggested by a study using 11 C-acetoacetate positron emission tomography (PET) imaging that showed that within 48 hours of the onset of fasting, there is a sevenfold to eightfold increase in brain uptake of ketones 4,145 . Moreover, whereas brain cell uptake of glucose is severely impaired in patients with AD, the cells remain capable of utilizing ketones 146 .…”
Section: Ims and Neurological Disordersmentioning
confidence: 99%
“…Every time they eat, the glycogen stores in their liver are replenished; liver glycogen provides 700–900 calories of glucose or energy, an amount that will last 10–14 hours in individuals who are not exercising. Subsequently, liver energy stores are depleted, circulating glucose levels remain low and adipose cells release fatty acids, which are converted in the liver to the ketone bodies β-hydroxybutyrate (BHB) and acetoacetate (AcAc), which are released into the blood and are used as energy substrates by neurons 4,5 (FIG. 1).…”
mentioning
confidence: 99%
“…usually 3% of brain energy requirements. Nevertheless, ketones are still the adult brain's preferred fuel so they spare brain glucose uptake for other uses (Courchesne-Loyer et al, 2017). Fourth, production of glucose and ketones from endogenous substrates is governed by insulin but insulin appears to have little or no effect on ketone production from exogenous MCT.…”
Section: Ketones and Brain Energy Metabolismmentioning
confidence: 99%
“…Our PET protocol involves sequentially assessing brain ketone uptake first (because 11 C is a short-lived radiotracer) followed by assessing brain glucose uptake with the tracer -18 F-flurodeoxyglucose. This provides a measure of brain uptake of both fuels within a three hour period in the same person on the same day, which is as comparable an assessment of both brain glucose and ketone metabolism as possible (Roy et al, 2012(Roy et al, , 2013Castellano et al, 2017;Courchesne-Loyer et al, 2017;Croteau et al, 2017).…”
Section: Keto-neurotherapeuticsmentioning
confidence: 99%
“…PET imaging using [ 11 C]acetoacetate ([ 11 C] AcAc ) can provide quantitative analysis of brain ketone utilization that can help uncover the role of ketone metabolism in early AD; such information could potentially lead to new preventive and therapeutic strategies (Authier et al, 2008; Courchesne-Loyer et al, 2016; Nugent et al, 2013). These promising translational imaging applications of [ 11 C] AcAc stimulated efforts for the development of a more robust and simple automated radiochemistry procedure.…”
Section: Introductionmentioning
confidence: 99%